2001
DOI: 10.1520/jfs15066j
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Suicide in a Large, Urban Area: Psychological, Demographic, and Situational Factors

Abstract: We examined all completed suicides by children and adolescents in Los Angeles County who died during 1996 and 1997. There were 46 subjects, aged 11 through 16. The majority of the decedents were males and over age 14. The predominant racial group was Hispanic. There was an almost even split between firearms and hanging as the means of death. Females had a statistically significantly higher rate of prior suicide attempts than males. Over one-third left a suicide note, almost one-half were noted to be depressed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 33 publications
3
27
3
2
Order By: Relevance
“…Therefore, an increased trend was recorded with increasing age, as has been previously reported [1,2,5,6]. It is noteworthy that there were no deaths for children under 12 years of age, in line with other studies [3,6,[14][15][16]. The majority of the victims were males, and the male to female ratio (4.25) was significantly higher than the ratio reported for other western countries [6,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, an increased trend was recorded with increasing age, as has been previously reported [1,2,5,6]. It is noteworthy that there were no deaths for children under 12 years of age, in line with other studies [3,6,[14][15][16]. The majority of the victims were males, and the male to female ratio (4.25) was significantly higher than the ratio reported for other western countries [6,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…The 2000s were marked by the significant increase of works, which can be justified by the significant hike of consummated suicides in childhood 12,14,[24][25][26][27][28][29][30][31][32] . They are case-control and cohort studies; international multi-center studies are developed and there is a technical rigor around the classification of deaths by suicide in children, seeking to gather and discuss aspects of bullying, depression and suicide.…”
Section: Literature In the Period 1980-2016mentioning
confidence: 99%
“…Countless studies have found that almost half of the children have recently had disciplinary problems at school 4,13,19,20,[24][25]27,[29][30][31]34,35 . Among the disciplinary problems, 25.3% failed in school grades, 18.3% dropped out of school and 16.3% were suspended from school 24 .…”
Section: Relationship Between School-related Factors and Suicide In Cmentioning
confidence: 99%
See 2 more Smart Citations